Law among nations : an introduction to public international law - Von Glahn, Gerhard, 1911-1997; Taulbee, James Larry, 1942- (New York : Routledge, Taylor & Francis Group, 2017)
"Offering a more accessible alternative to casebooks and historical commentaries, Law Among Nations explains issues of international law by tracing the field's development and stressing key principles, processes, and landmark cases.This comprehensive text eliminates the need for multiple books by combining discussions of theory and state practice with excerpts from landmark cases. The book has been updated in light of the continuing revolution in communication technology, the dense web of linkages between countries that involve individuals and bodies both formal and informal; and covers important and controversial areas such as human rights, the environment, and issues associated with the use of force.Renowned for its rigorous approach and clear explanations, Law Among Nations remains the gold standard for undergraduate introductions to international law."--Back cover.
The nature of international law -- Development of law among nations -- Sources of the law -- International agreements -- International legal process -- The relationship between international and municipal law -- Subjects of international law : recognition -- Rights and duties of international legal persons -- Nationality -- Principles of jurisdiction -- State responsibility -- The law of the sea -- Jurisdiction over air space and outer space -- Agents of international intercourse immunities -- The individual and international law : human rights -- International criminal law -- Adjudication -- International law and protection of the environment -- The use of force -- International humanitarian law : war crimes -- War crime tribunals.
Includes bibliographical references and indexes.
Keywords: International law; International law; 86.80 international law: general